2018
DOI: 10.1111/izy.12178
|View full text |Cite
|
Sign up to set email alerts
|

Orang‐utans Pongo spp in Asian zoos: current status, challenges and progress towards long‐term population sustainability

Abstract: Bornean orang‐utans Pongo pygmaeus sspp and Sumatran orang‐utans Pongo abelii are Critically Endangered species, in rapid decline throughout their ranges in Indonesia and Malaysia. Although substantial populations are well documented in Western zoos, comparatively little is known about those in the East, despite their endemism to the region. Here, the status and distribution of orang‐utans in Asian zoological institutions are outlined, accounting for 466 orang‐utans at 77 institutions in 13 geographic location… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…In Europe, EAZA maintains that because zoos have been 'mixing' subspecies for a long time, there is little chance of unravelling admixtures (Bemment, 2018). Across Asia, no consistent management plan exists, not least because a 2018 study found that 14% of zoo-kept orangutans were of completely unknown origin, while the assigned provenance of another 7% is questionable due to an unreliable test (Banes et al, 2018). Thus, captive hybrid apes, like other 'unloved' subjects of conservation, often have their welfare compromised for the sake of the population.…”
Section: How Are Population-level Concerns and Welfare Of Individual Animals Balanced In Conservation Breeding?mentioning
confidence: 99%
“…In Europe, EAZA maintains that because zoos have been 'mixing' subspecies for a long time, there is little chance of unravelling admixtures (Bemment, 2018). Across Asia, no consistent management plan exists, not least because a 2018 study found that 14% of zoo-kept orangutans were of completely unknown origin, while the assigned provenance of another 7% is questionable due to an unreliable test (Banes et al, 2018). Thus, captive hybrid apes, like other 'unloved' subjects of conservation, often have their welfare compromised for the sake of the population.…”
Section: How Are Population-level Concerns and Welfare Of Individual Animals Balanced In Conservation Breeding?mentioning
confidence: 99%
“…Many of the zoos and aquariums in Asia are surrounded by regions of exceptionally high biodiversity: biodiversity hotspots (Le Roux et al 2019). Many of the species arriving in zoological collections are the result of confiscations of animals (Banes et al 2018). Species include great apes (Banes et al 2018), gibbons, turtles, and tortoises (Rivera et al 2021).…”
Section: Influences Of Asian Collection Planningmentioning
confidence: 99%
“…Many of the species arriving in zoological collections are the result of confiscations of animals (Banes et al 2018). Species include great apes (Banes et al 2018), gibbons, turtles, and tortoises (Rivera et al 2021). The accession of great numbers of new animals places pressure on zoological facilities in terms of space, resources, and staffing.…”
Section: Influences Of Asian Collection Planningmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, ex-situ orang-utans in zoos might serve as model populations for studying the effects of human intervention. Approximately 1100 orang-utans live in zoos worldwide, although numbers are probably higher in developing nations and in range countries [ 12 ]. Zoo populations of orang-utans are known to be highly admixed.…”
Section: Introductionmentioning
confidence: 99%